Fifteen lectures on Showa Japan road to the Pacific war in recent historiography - Tsutsui, Kiyotada 1948-; Noda, Makito; Narum, Paul (Japan library (Shuppan Bunka Sangy?o Shink?o Zaidan), 2016)
"Why did Showa Japan rush to war? Where did Japan fail? This compilation of the most up-to-date studies by 15 spirited Japanese historians tries to find answers to these questions. Each chapter contains a list of selected reference books with brief annotations for the benefit of readers who wish to study more about the subject. These are the best lectures on prewar Showa history for readers who want to know the truth." from back cover.